53.083.1 CLASSIFICATION AND ANALYSIS OF LEVEL MEASUREMENT METHODS: 1Mahmudjonov M.M., 2Muminov Kh.D., 3Tilavkhanova L.R. - Mahmudjonov, Mirolim; Muminov , Xolmurod; Tilavkhanova L.R. (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents the classification of level measuring instruments and level sensors used as their sensitive elements. It describes the operating principles of electromechanical, electrical, optoelectronic, radio wave, acoustic and ultrasonic, hydrostatic, and radioisotope level sensors, providing examples of these devices. The advantages and disadvantages of using these sensors are also discussed. Additionally, the article analyzes the accuracy indicators of level measuring instruments and the factors influencing the results obtained from them